2020
DOI: 10.1111/ijd.15299
|View full text |Cite
|
Sign up to set email alerts
|

The clinico‐epidemiological characteristics and therapeutic experience of 152 patients with cutaneous sporotrichosis: a 10‐year retrospective study from India

Abstract: Background Cutaneous sporotrichosis, a subcutaneous mycosis because of Sporothrix schenckii, is sporadic worldwide with local hyperendemic pockets. Objectives To study clinico-epidemiological and therapeutic aspects of sporotrichosis in our clinic. Methods We retrospectively analyzed medical records of 152 (M:F 52:100) patients with cutaneous sporotrichosis managed during 2010-2019. Results All patients were involved in agricultural activities, and 63.2% were aged 21-60 years. Women outnumbered men by nearly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…However, there are considerable regional variations between men and women. Women have approximately twice the morbidity as men in India due to greater participation in agricultural activities 11 . Men have higher morbidity than women in South Africa, with a male‐to‐female ratio of 3:1, this is because they often engage in outdoor activities and mining labour 12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are considerable regional variations between men and women. Women have approximately twice the morbidity as men in India due to greater participation in agricultural activities 11 . Men have higher morbidity than women in South Africa, with a male‐to‐female ratio of 3:1, this is because they often engage in outdoor activities and mining labour 12 .…”
Section: Discussionmentioning
confidence: 99%
“…phagocytosis and biofilm inhibition in the yeast-like and filamentous phases. 85 , 86 The anti-inflammatory effect in vivo seems to be related to cytokine regulation, with increased levels of IL-10 and IL-35. 87 It is likely that the anti-inflammatory and immunomodulatory effects are responsible for faster clinical improvement than with itraconazole or terbinafine.…”
Section: Resultsmentioning
confidence: 99%
“…Trauma is usually needed for fungus entry. 2 Sharma et al 29 reported 152 sporotrichosis cases, 48% of which had a history of trauma. Comparatively, among patients who visited our hospital, 26.4% reported a definite history of trauma (stab wounds by reed, corn stalk, or wood).…”
Section: Dovepressmentioning
confidence: 99%